Motivations of crowdsourcing contributors - Luiz Fernando Silva Pinto; Carlos Denner dos Santos (Innovation & Management Review, 2018)
Purpose: This study aimed at analyzing the factors that induce the intention of contribution by participants in crowdsourcing initiatives. Design/methodology/approach: This study is an explanatory investigation using a quantitative approach. In the second stage, an exploratory study was carried out. Data were obtained through online questionnaires available to the contributors of two platforms, and results were obtained from a regression analysis. Findings: The results revealed a greater importance given by participants to intrinsic motivational factors (learning, fun and satisfaction) compared with the extrinsic motivational factor (acknowledgment). Monetary rewards proved irrelevant in this process, whereas attitude and self-efficacy proved good predictors of the intention of contribution in crowdsourcing initiatives. Originality/value: No study, as far as the authors' knowledge extends, has been undertaken to understand what motivations are more relevant in the context of crowdsourcing platforms using multiple theories.
Keywords: 650; Innovation; Crowdsourcing; Crowdsourcing contributors; Intrinsic and extrinsic motivations; Planned behavior theory